2021
DOI: 10.3389/fnhum.2021.757579
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Treating Dystonia: A Systematic Review of Targets, Body Distributions and Etiology Classifications

Abstract: Background: Deep brain stimulation (DBS) is a typical intervention treating drug-refractory dystonia. Currently, the selection of the better target, the GPi or STN, is debatable. The outcomes of DBS treating dystonia classified by body distribution and etiology is also a popular question.Objective: To comprehensively compare the efficacy, quality of life, mood, and adverse effects (AEs) of GPi-DBS vs. STN-DBS in dystonia as well as in specific types of dystonia classified by body distribution and etiology.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 54 publications
2
25
1
Order By: Relevance
“…DBS has been widely used for treating dystonia, and therapeutic targets of the global pallidus internus (GPi) and the STN seem to have similar efficacy 6 . Kwong et al 3 concluded that GPi‐DBS responses varied among different monogenic forms of dystonia, and it did benefit a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBS has been widely used for treating dystonia, and therapeutic targets of the global pallidus internus (GPi) and the STN seem to have similar efficacy 6 . Kwong et al 3 concluded that GPi‐DBS responses varied among different monogenic forms of dystonia, and it did benefit a majority of patients.…”
Section: Discussionmentioning
confidence: 99%
“…DBS has been widely used for treating dystonia, and therapeutic targets of the global pallidus internus (GPi) and the STN seem to have similar efficacy. 6 Kwong et al 3 concluded that GPi-DBS Video 1. Segments 1, 2, and 3: patient with dystonia-deafness syndrome attributed to a β-actin (ACTB) gene mutation presenting with dystonic gait, cervical dystonia, and scoliosis 5 days before and 7 and 12 months after deep brain stimulation of the bilateral subthalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…DBS is the preferred treatment modality for patients with isolated dystonia without CNS degeneration or insult is because it is reversible. [22][23][24][25][26][27] However, the advantages of DBS in patients with acquired/heredodegenerative dystonia are not definite. 26,28,29 A recent multicenter, single-arm, randomized, double-blind crossover trial on the effect of DBS in pediatric dystonia patients with dyskinetic cerebral palsy concluded that the evidence is insufficient to recommend DBS as routine treatment for these patients.…”
Section: Role Of Pallidotomy In the Era Of Dbsmentioning
confidence: 99%
“…[22][23][24][25][26][27] However, the advantages of DBS in patients with acquired/heredodegenerative dystonia are not definite. 26,28,29 A recent multicenter, single-arm, randomized, double-blind crossover trial on the effect of DBS in pediatric dystonia patients with dyskinetic cerebral palsy concluded that the evidence is insufficient to recommend DBS as routine treatment for these patients. 28 A recent Cochrane review of the role of DBS in dystonia also concluded that the evidence in the available literature is insufficient to draw any conclusions about the advantages of DBS in children and adolescents with dystonia and secondary dystonia.…”
Section: Role Of Pallidotomy In the Era Of Dbsmentioning
confidence: 99%
“…It is also known that STN-DBS is equally effective in treating idiopathic and hereditary dystonias compared to GPi-DBS ( 45 47 ), although the stimulation parameters could differ from those in Parkinson's disease ( 48 ). The rationale for this target is not clearly explained, asin dystonia direct pathway predominance must be met with increasing indirect pathway including STN.…”
Section: New Targets For Deep Brain Stimulationmentioning
confidence: 99%